APROXIMACIÓN CRÍTICA A LA REGULACIÓN DE LA SUBCONTRATACIÓN DE LAS ACTIVIDADES COMPLEMENTARIAS VÍA INTERMEDIACIÓN LABORAL - Castillo Pastor, Carolina (2022)
This article has presented the analysis, from a critical point of view, of the possibilities of contracting the complementary activities of a user company to be carried out by a third party based on the normative regulation of labour intermediation in force in our country, which is considered ambiguous. To do so, what labour intermediation is will be defined and its legal nature will be analyzed, differentiating it from the outsourcing of services. The objective is to define the activities that can be outsourced by means of that figure and answer various questions raised in relation to the exercise by the user company of the powers of management and supervision over the outstanding personnel and to the autonomy of the intermediary entity; Issues that result given that the current normative regulation in our country is confusing. Finally, suggestions were made on normative modifications with the objective that the Peruvian labour law regarding the subcontracting of complementary activities of a company remain coherent with the legal nature of labour intermediation and outsourcing of services.